Prevention of acute mountain sickness by low positive end-expiratory pressure in field conditions - Launay, Jean-Claude; Nespoulos, Olivier; Guinet-Lebreton, Angélique; Besnard, Yves; Savourey, Gustave (Scandinavian Journal of Work, Environment & Health, 2004)
' ' OBJECTIVES ': 'This study evaluates the ability of positive end-expiratory pressure (PEEP), a nonpharmacological method, to prevent the occurrence of acute mountain sickness during two ascents of Mount Blanc. ' ' METHODS ': 'In a random order (once with PEEP and once without), PEEP was administered or not to eight subjects during two ascents of Mount Blanc. Scores for acute mountain sickness were quantified using the Lake Louise acute mountain sickness scoring system, and oxygen arterial blood saturation by pulse oxymetry (SpO2), heart rate, and systolic and diastolic blood pressures were also measured. ' ' RESULTS ': 'The decrease in the prevalence of acute mountain sickness indicated that the PEEP system was effective, one case (12.5%) occurring among the eight participants with PEEP and six cases (75%) occurring among the eight without PEEP (P<0.01). The severity of the cases also decreased (P<0.01). Heart rate and blood pressure did not significantly vary, whereas the SpO2 tended to be higher with PEEP (P=0.07). ' ' CONCLUSIONS ': 'This field study shows that PEEP could be an efficient method with which to prevent acute mountain sickness without adverse effects. However, the ergonomics of the PEEP system must be improved to make its use more practical in the future.
Keywords: acute mountain sickness; expiratory pressure; field study; high altitude environment; low barometric illness; low positive end-expiratory pressure; nonpharmacological; prevention